Study of Structural and Optical Behaviour of Silver -Copper Bimetallic Nanoparticles - Ponrani, R. S. M.; Nancy, D. E.; Rejith, S. G.; Durai, S. C. V. (Physics and Chemistry of Solid State, 2024)
Silver-based nanomaterials have proven interesting and promising material for numerous applications such as biosensor, antimicrobial, anticancer agent, catalyst, food and water treatment, energy storage devices etc.In this study, nanoparticles of Silver and Copper were prepared by chemical reduction method, using hydrazine hydrate and Sodium borohydride as reducing agent. Fine powder of Ag-Cu nanoparticles (NPs)was obtained. The structural analysis of the sample wasdone using Powder XRD, SEM and TEM images and particle size analysis by DLS.The chemical purity and the elemental compositions of synthesized NPs were studied using SEM-EDX. Optical properties of the Ag-Cu NPs were analyzed using UV-DRS spectrum and FTIR spectrum. PXRD reveals that the NPs are highly crystalline in nature.The average crystallite size is30 nm. SEM and TEM images confirm the spherical morphology and the particle size is in nm. The DLS-particle size analyzer shows the size distribution of most of the NPs ranging from 9 nm to 100 nm. The EDX analysis reveals the percentage of elemental composition as 14.71, 9.06 and 76.23 for silver, copper and oxygen respectively. UV-DRS spectrum shows the absorption maximum occur at 371 nm. Due to the synergistic effect of silver and copper, there is blue shift in the absorption maximum. The IR spectrum discloses the metal oxide bond in the synthesized NPs.